2020
DOI: 10.1111/fog.12489
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of the daily growth traits of the prerecruits of a small pelagic fish in response to environmental drivers

Abstract: These species also play an important economic role, representing approximately 37% of the global landing of wild marine fish, although they are mainly caught for the production of fishmeal and fish oil for agricultural, aquacultural, and industrial purposes (Alder, Campbell, Karpouzi, Kaschner,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Comparing rate of growth obtained in this study with other data showed agreement [37] or disagreement [39] alternatively. As linked to trophic conditions, the ecological and hydrological local characteristics of the water masses strongly influence the species' rate of growth [84][85][86][87][88]. Whatever the case, a negative allometric growth indicates that food is a first order constraint for this species, and this generally applies to deep-water species [89][90][91][92].…”
Section: Corollary Biological Datamentioning
confidence: 99%
“…Comparing rate of growth obtained in this study with other data showed agreement [37] or disagreement [39] alternatively. As linked to trophic conditions, the ecological and hydrological local characteristics of the water masses strongly influence the species' rate of growth [84][85][86][87][88]. Whatever the case, a negative allometric growth indicates that food is a first order constraint for this species, and this generally applies to deep-water species [89][90][91][92].…”
Section: Corollary Biological Datamentioning
confidence: 99%